Effects of laterality on the technical/tactical behavior in view of the results of judo fights - Sterkowicz, S.; Lech, G.; Blecharz, J. (Archives of Budo, 2010)
Background and Study Aim: Laterality plays an important role in sports, especially in ball or combat sports. High skill level of athletes with left-side dominance allows them to gain a tactical advantage over their opponents, and to increase their chances for success. The awareness of such advantage boosts athlete`s self-confidence in combat situation. The purpose of this study was to determine: (a) laterality of upper and lower limbs and its relation to preferred directions of attack in fight; (b) relation between a preferred attack direction as well as resources of techniques applied in combat and the level of achievement among judo athletes. Material/Methods: Ninety judoists, U15 years old, who had trained for the average 4.5 years, participated in the International Tournament. An interview carried out with the participants provided data about their handedness or footedness while performing technical elements of judo. Four hundred twenty eight technical-tactical actions were recorded and analyzed. The most common were throws (86.2%). Results: Left-handed athletes, who preferred more forward right throws, were more effective than the right-handed ones. Technical profile of the right-footed athletes was similar to right-handed ones. The left-footed athletes differed as far as attack profile was concerned. The profile was characterized by regular intensity of back left throws, forward right throws and forward left throws. The least common were back right throws in all groups. Conclusions: Laterality of upper and lower limbs is strongly related to the choice of dominant attack directions in fight. Left-sided athletes had significantly more chances to win a medal than their right-sided counterparts.